2020
DOI: 10.1177/2158244020935899
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interprofessional Primary Care Practice on Patient Outcomes: A Scoping Review

Abstract: Systematic reviews have provided some insight into the impact of interprofessional collaborative practice on patient outcomes. Despite strong interest in interprofessional collaborative practice, relatively little is known about its impact in primary care settings. This scoping literature review describes the essential elements of an interprofessional primary care practice and explores what is known about its impact on patient care including clinical, humanistic, and economic outcomes. We completed a review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…We identified 6316 articles from the 2013-2018 searches and 175 articles from other sources. After removing duplicates, the review teams screened 3543 titles or abstracts then reviewed 170 abstracts or full-texts to assess 63 articles for eligibility, including the 12 relevant articles from the previous scoping review 12 and 5 from the abbreviated search update (2018 to March 2020). Of these, 13 records were excluded for having 3 or fewer health professions or no usable outcome measures, leaving 50 articles retained in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 6316 articles from the 2013-2018 searches and 175 articles from other sources. After removing duplicates, the review teams screened 3543 titles or abstracts then reviewed 170 abstracts or full-texts to assess 63 articles for eligibility, including the 12 relevant articles from the previous scoping review 12 and 5 from the abbreviated search update (2018 to March 2020). Of these, 13 records were excluded for having 3 or fewer health professions or no usable outcome measures, leaving 50 articles retained in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…A previous scoping review (2000-2013) examined the breadth of information on ICP in primary care and reported broad consequences associated with patient outcomes. 12 This review, without meta-analysis, found 8 studies reporting positive differences in HbA 1c and 10 reporting positive differences in BP when ICP was compared with controls. Conversely, 6 additional studies reported no differences in HbA 1c , and 3 reported no differences in BP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research was carried out in a public higher education institution, located in Botucatu-SP, Brazil. In this context, in 2017 the PRMSF started to discuss the theoretical background of the IECP (1)(2)5,8,12) in theoretical and theoretical-practical activities, in the tutoring meetings, and in the case discussions It is important to highlight that the rigors of the theoretical-methodological point of view were followed to carry out a research study with a qualitative approach.…”
Section: Methodsmentioning
confidence: 99%
“…The questions were elaborated from publications with a qualitative approach and object of similar studies (1)(2)5,8,12,14,21) that considered items to be explored in the composition of the questions such as those described in Figure 1, in which they deal with the following: the reason for the professional choice, the experiences during graduation and residency in relation to the IECP, and the professional categories that stood out in their teachinglearning process.…”
Section: Each Prmsf Class Is Divided and Distributed Into Fourmentioning
confidence: 99%